Biopython: Comparing the DNA Polymerase I (polA) Gene of Thermophilic, Mesophilic, and Psychrophilic Bacteria - Adam, Chaidir (BiosciED: Journal of Biological Science and Education, 2021)
Biopython is a specialized Python tool for computational molecular biology. Various computational molecular analysis that can be performed using Biopython, such as reconstructing phylogenetic trees, multiple sequence analysis, generating complementary sequences, counting amino acids, etc. This technical notes paper describes in detail the procedures computational DNA sequence analysis using Biopython. The DNA polymerase I (polA) gene sequences of bacteria were used in this study to compare the differences between Thermophilic, Mesophilic, and Psychrophilic bacteria.